Toxicity of cadmium based and cadmium free quantum dots in primary cultured zebrafish hepatocytes - BİLGİSEVEN, IRMAK; MUTLU, ÖZAL; GÜLSOY, NAGİHAN (My University, 2020)
Quantum Dots (QDs) are one of the most im-portant nanomaterials in nanotechnology owing to their unique physicochemical properties. A conven-tional QD contains Cd2+ in its core and in order to reduce its toxicity Cd-core/ZnS-shell and Cd-free QDs were produced. However, ZnS shell was not found as protective as predicted. Also, still not much is known about the toxicity of Cd-free QD. In this paper, we evaluated and compared the cytotoxicity and genotoxicity of three types of QDs (Cd-based core, Cd-based core/shell, and Cd-free QDs) in pri-mary cultured zebrafish hepatocytes. We show that Cd-based QDs significantly decreased cell viability whereas Cd-Free QDs caused a significant increase in cell viability in 24h. Moreover, ZnS shell reduced Cd2+ ion release into the cell but did not effectively prevent the cell from cytotoxic or genotoxic effects of the QD. Although the effects of Cd-based and Cd-Free QDs on cell viability were different, they both induced reactive oxygen species (ROS) production, DNA strand breaks and Rad51 downregulation in primary cultured zebrafish hepatocytes, revealing that they induce oxidative stress in these cells. To the best of our knowledge, this is the first report on the comparative toxicity evaluation of Cd-based with core and core/shell type, Cd-free QDs and CdCl2 by assessing ROS production, DNA damage and Rad51 expression.
Keywords: Yaşam Bilimleri; Çevre Biyolojisi; Ekotoksikoloji; Temel Bilimler; Life Sciences; Environmental Biology; Ecotoxicology; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; Biyoloji ve Biyokimya; ÇOK DİSİPLİNLİ BİLİMLER; BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; MULTIDISCIPLINARY SCIENCES; BIOLOGY; Multidisipliner; Multidisciplinary; Cadmium free quantum dots; Zebrafish; Cadmium; COMET; Rad51